2017
DOI: 10.1021/acs.jpcb.7b10310
|View full text |Cite
|
Sign up to set email alerts
|

Piecemeal Rekindling of Coumarin 6 Fluorescence on Stepwise Unfolding of Protein by Surfactant

Abstract: Coumarin 6 (C6) briskly aggregates in water, and as a result, rapidly loses fluorescence. However, vicinal hydrophobic cavity can induce disintegration of the aggregates, and thus reviving the fluorescence. It is shown that carrier protein, such as bovine serum albumin (BSA), can disintegrate the microcrystals of C6 to smaller fragments and trap them inside the hydrophobic domain of the folded protein. This results into a 12-fold enhancement in the fluorescence signal of C6. However, on unfolding BSA by micell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…This consolidates the occurrence of ICT inside the niosomal bilayer. , The results from the time-resolved fluorescence decay of C6 in an aqueous environment are intriguing as they reflect the excited state processes in detail. Raw data of the emission decay of C6 fit a bi-exponential routine in bulk water as well as in niosomes (Figure B). In bulk water, C6 undergoes self-aggregation, and hence the aggregates coexist with the individual C6 molecules. C6 in the aggregated state decays faster compared to the individual units .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…This consolidates the occurrence of ICT inside the niosomal bilayer. , The results from the time-resolved fluorescence decay of C6 in an aqueous environment are intriguing as they reflect the excited state processes in detail. Raw data of the emission decay of C6 fit a bi-exponential routine in bulk water as well as in niosomes (Figure B). In bulk water, C6 undergoes self-aggregation, and hence the aggregates coexist with the individual C6 molecules. C6 in the aggregated state decays faster compared to the individual units .…”
Section: Resultsmentioning
confidence: 95%
“…Self-aggregation of coumarin dyes is readily observed in several occasions due to the structural features of the molecule. Typically, the planar coumarin skeletons are susceptible to aggregation via strong π–π stacking interactions leading to aggregation-caused quenching (ACQ) of photoluminescence (PL) and weakening the activity of optoelectronic devices and many other exciton-controlled performances. ,,, The coumarin member used in the present study is C6 (Figure A) that aggregates readily in water even at 1 μM concentration and hence substantially loses its PL . However, this lost PL can be revived by several host–guest chemistry-based techniques following hydrophobic interactions. Hence, we have applied the multilamellar niosome vesicles that followed the same mechanism to disintegrate the aggregated C6 molecules, which encapsulate inside the membrane (Figure A), and hence the lost PL is revived (Figure B). The double-humped absorption spectrum of C6 in neat water gradually reduces to a single peak (Figure C), indicating the disruption of the aggregates that absorb at 500 nm. , There is a remarkable variation in the fluorescence spectrum of C6, with a considerable change in the structure accompanied by a significant blue shift of 50 nm (Figure D,E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique could be successfully applied in energy transfer reactions in the excited state. 36 It has been shown that the rate of excited state electron transfer is much faster compared to that of the ground-state phenomenon because of the proximity and the resonance factors. 38 Thus, adsorption of a guest system to a host, either physically or chemically, is likely to undergo such consequences.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This process considerably lowers the fluorescence yield of C6 with time . In a series of studies, we have shown several ways to revive the lost fluorescence of C6 in water by using various hosts that have relatively hydrophobic cavities. , Using biocompatible hosts, such as, β-cyclodextrin (β-CD), micelles, proteins, and single-walled carbon nanotubes, the microcrystalline states of C6 could be broken and the fluorescence emission could be revived. This technique could be successfully applied in energy transfer reactions in the excited state …”
Section: Introductionmentioning
confidence: 99%